The Baldrige Award's falling fortunes. Issue 6 (5th August 2019) - Cook, David; Zhang, Weiyong
Abstract : Purpose: The purpose of this paper is to explore two explanations for the Baldrige Award's decline. The management fashion literature suggests that it is a waning management fad, and the marketing choice literature suggests the likely presence of an ISO 9000 substitution effect. Design/methodology/approach: This exploratory study utilizes data collected on Baldridge Award applications, publications, ISO 9000 certifications and economic indicators. These data are contrasted to explore patterns and trends, and correlation analyses conducted to reveal the plausibility of the fad and substitution effect explanations for the Baldrige Award's decline. Findings: Data analysis confirms the Baldrige Award's prolonged decline and strongly suggests it is in the final stage of a management fashion life cycle with support provided for the presence of an ISO 9000 substitution effect. Research limitations/implications: Many organizations have shifted their attention away from the Baldrige as a means to quality and performance excellence, and there is evidence that the ISO 9000 standards are a viable substitute. Practical implications: The Baldrige Program has served its purpose with the Baldrige Award being the pinnacle of recognition for performance excellence achievement. However, the Award is in decline and the Baldrige Program is on a path to financial exigency. The Baldrige must be reframed to recover its role as the preeminent approach to performance excellence. Originality/value: The paper satisfies the need to examine potential causes for the diminishing role of the Baldrige Award and challenges both academicians and practitioners to reexamine the Baldrige Program.